(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates knowledge of personal hygiene among students with hearing impairment in special schools in Rivers-East Senatorial District, Rivers State. The study adopted the descriptive research design. The study was guided by three research questions and three null hypotheses. The population of the study comprised sixty-two (62) students with hearing impairment in special schools and inclusive schools in the area. The sample size was 62 students with hearing impairment. The census sampling technique was used for the study. The instrument for data collection was a self-structured questionnaire, titled: “Knowledge of Personal Hygiene Questionnaire’’ (KPHQ)”. The reliability of the instrument was determined through test re-test reliability method which yielded a reliability index of r=0.81. Mean and standard deviation were used to answer the research questions while Independent sample t-test was used to test the null hypotheses at 0.05 level of significance. The study revealed that there was high level of knowledge of personal hygiene among students with hearing impairment in special schools in Rivers-East Senatorial District based on gender. It was further revealed that there was no significant difference in the mean rating of male and female students on their level of knowledge of personal hygiene among students with hearing impairment in special schools in Rivers-East Senatorial District. It was recommended among others that; Parents and teachers should be encouraged to continue giving correct and appropriate personal hygiene information to students with hearing impairment and other areas of disabilities.